Self‐Assembling of Fmoc‐GC Peptide Nucleic Acid Dimers into Highly Fluorescent Aggregates. Issue 18 (28th February 2018) - Avitabile, Concetta; Diaferia, Carlo; Della Ventura, Bartolomeo; Mercurio, Flavia Anna; Leone, Marilisa; Roviello, Valentina; Saviano, Michele; Velotta, Raffaele; Morelli, Giancarlo; Accardo, Antonella; Romanelli, Alessandra
Abstract: The study of molecules that self‐assemble through noncovalent interactions is one of the most attractive topics in supramolecular chemistry. The use of short peptides or modified nucleotides as building blocks for the aggregates is particularly intriguing because these are very easy to synthesize; moreover, subtle changes in the chemical structure of such building blocks may drastically affect the properties of the aggregates. The ability of peptide nucleic acids (PNA) to aggregate has been very little explored, despite its practical applications. In this work we investigated the self‐assembling properties of a PNA dimer, conjugated at the N‐terminus to a fluorenylmethoxycarbonyl group. This PNA dimer forms nano‐aggregates at low concentration in CHCl3 /CH3 OH mixtures. The aggregates retain very interesting fluorescent properties (high quantum yield in the visible region with lifetimes on the nanosecond scale), which make them promising materials for applications in optoelectronics. Abstract : PNAs come together : The self‐assembling properties of peptide nucleic acids (PNA) dimers, conjugated at the N‐terminus to a fluorenylmethoxycarbonyl group are described (see figure). The results show that Fmoc promotes the aggregation of PNA dimers.